Composite impulsivity-related domains in college students. (July 2017) - Khadka, Sabin; Stevens, Michael C.; Aslanzadeh, Farah; Narayanan, Balaji; Hawkins, Keith A.; Austad, Carol S.; Raskin, Sarah A.; Tennen, Howard; Wood, Rebecca M.; Fallahi, Carolyn; Potenza, Marc N.; Pearlson, Godfrey D.
Abstract: Impulsivity is a complex, multidimensional construct with prior theoretically and empirically derived characterizations of impulsivity-related behaviors varying considerably among studies. We assessed college students (N = 440) longitudinally with five impulsivity-related self-reported assessments and two computerized behavioral measures. Using a combination of exploratory and confirmatory factor analysis (CFA), we derived then validated several composite impulsivity-related domains (CIRDs). These factors replicated, in large part, findings from a previous study conducted by our group in an independent sample that used a similar analytical approach. The four CIRDs derived in current study are: 'Impulsive action', 'Approach/Appetite Motivation', 'Impulsivity/Compulsivity' and 'Experience and thrill seeking/Fearlessness'. Subsequent psychometric analyses found these CIRDs were relatively stable over the two-year period. Moreover, multiple regression analysis found that CIRD profiles associated with clinical and behavioral characteristics including anxiety, depression, attention deficit hyperactivity disorder and substance use symptomology. Overall, our data suggest that empirically-derived CIRDs have potential for organizing previous impulsivity-related constructs into a more naturalistic framework where distinct constructs are often expressed together in the same individuals. This framework might facilitate future research of neuropsychiatric disorder risk and etiology.